Occurrence frequency of selected non-metrical features of cranium depending on cribra orbitalia and the equipment of graves - Bergman, Paweł (Anthropological Review, 1986)
The analysis of skulls (N = 436) from the aligned cemetery in Milicz. Lower Silesia (12th-14th CC.) gave the following results. The frequencies of appearance of certain non-metric traits may undergo changes caused by a morbid factor (anaemia as a result of iron deficiency). The analysis of frequencies of appearance of cribra orbitalia shows that the presence of grave equipment versus lack of such equipment indicates a higher level of living conditions, at least in the sense of better health and nutritional status of the deceased individuals. Anaemia and its effects increased probably mortality especially in younger individuals (aduiius group) who, at the same time, existed in worse living conditions. No differences were found in frequencies of appearance of the eight non-metric traits between individuals from equipped and non-equipped graves. However, the frequencies of appearance of ossicula suturae lambdoideae show statistically significant differences. It is emphasized that the multivariate distances between populations may point not only toward ethnic or genetic differences between them but also toward differences conditioned environmentally.